CONSIDERATIONS ON THE INCIDENCE OF JUDO INJURIES - Chirazi M.; Babiuc I. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2017)
The practice of high performance sport leads to the appearance of all sorts of injuries with varying degrees of severity, caused by a multitude of factors. Most frequent injuries usually occur in contact sports. The decrease in the number of injuries is one of the constant concerns of the management authorities in most sports. The latest amendments of the judo regulations have led to improvements as far as accidents are concerned. Our study deals with the evolution of judo injuries in comparison with injuries during the practice of other sports over a period of several years, as well as with the identification of the causes which determined the occurrence of injuries. Our research paper also aims at establishing certain guidelines for the prevention of injuries, based on causes. Our research relies on the analysis of a significant number of scientific articles which deal with this topic, as well as on the cases we have identified in several judo competitions during this past year.